2022
DOI: 10.1001/jama.2022.6421
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Considerations for the Inclusion of Patient-Reported Outcomes in Clinical Research

Abstract: IMPORTANCE Patient-reported outcomes (PROs) can inform health care decisions, regulatory decisions, and health care policy. They also can be used for audit/benchmarking and monitoring symptoms to provide timely care tailored to individual needs. However, several ethical issues have been raised in relation to PRO use. OBJECTIVE To develop international, consensus-based, PRO-specific ethical guidelines for clinical research. EVIDENCE REVIEWThe PRO ethics guidelines were developed following the Enhancing the Qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…There has been some discussion about ethical collection and use of PROs in clinical care, focused on the integrating PRO data collected during research into patients' electronic health records, with options ranging from no disclosure to a detailed informed consent process including an opt-in requirement [22][23][24]. A set of ethical guidelines for research including PROs has recently been published [25], but they do not specify how research PROs can be integrated into care [25]. In pediatrics, limited attention has been paid to ethical questions surrounding PRO collection and data sharing in cohort or registry studies where consent and assent, child and family preferences, and clinical practice guidelines may change over time (i.e., in accordance with a child's age or capacity to provide consent).…”
Section: Existing Guidancementioning
confidence: 99%
“…There has been some discussion about ethical collection and use of PROs in clinical care, focused on the integrating PRO data collected during research into patients' electronic health records, with options ranging from no disclosure to a detailed informed consent process including an opt-in requirement [22][23][24]. A set of ethical guidelines for research including PROs has recently been published [25], but they do not specify how research PROs can be integrated into care [25]. In pediatrics, limited attention has been paid to ethical questions surrounding PRO collection and data sharing in cohort or registry studies where consent and assent, child and family preferences, and clinical practice guidelines may change over time (i.e., in accordance with a child's age or capacity to provide consent).…”
Section: Existing Guidancementioning
confidence: 99%
“…Increasingly, research ethics committees and institutional review boards, in their assessment of PRO research, are considering the burden of PRO collection on study participants 96 . An objective assessment of the potential burden could assist such committees in their decision-making process.…”
Section: Perception and Assessment Of Respondent Burdenmentioning
confidence: 99%
“…8 A guideline for the ethical considerations in the use of patient-reported outcomes has been published. 9 How Was a Patient-Reported Outcome Measure Applied in This Case?…”
Section: Limitations or Alternatives To Using A Patient-reported Outc...mentioning
confidence: 99%
“…There are international guidelines for high-quality trial protocols involving patient-reported outcome measures and for reporting the results of patient-reported outcome measure–based end points in clinical trials . A guideline for the ethical considerations in the use of patient-reported outcomes has been published …”
Section: Limitations or Alternatives To Using A Patient-reported Outc...mentioning
confidence: 99%